The Recurring Issue of Aviation English Test Validity: Echoes from Test-takers and Assessors of the English for Aviation Language Testing System in Algeria - Assassi , Tarek; Ghodbane, Tarek (English Studies at NBU, 2023)
The English for Aviation Language Testing System (EALTS) is one of the international tests for pilots wishing to operate in international airspace. This test presents a wide range of difficulties for Algerian pilots, but little research has been conducted to estimate its validity. This paper seeks to answer two questions: (1) What are test-takers perspectives on the EALTS test construct? and (2) What is the assessors’ perception of the testing procedure and test validity? A descriptive study was conducted using qualitative data from a semi-structured questionnaire for ten pilots and a semi-structured interview for three certified assessors and four university researchers. The authors used ’first-hand’ data from the targeted sample to cross-check results’ validity through triangulation. The results show specific difficulties from an affective dimension, such as stress and anxiety caused by inefficient preparation and unfamiliarity with test tasks. A different interpretation of ICAO descriptions using the rating scale is another issue noted by assessors. Additionally, technical issues with the computer-based listening test and non-compliant features of the test contents with features of the target situation language use are among the main issues noted by both test-takers and assessors.